Experiências locais de uso do Sistema Eletrônico de Editoração de Revistas (SEER): o caso da Universidade Federal do Pará (UFPA) - BARROS, Diego Bil Silva (2017)
This study aimed to examine how it has been given the use of Journal Publishing System (SEER) by the scientific institutions of the Federal University of Pará (UFPA) However, we sought to ascertain to what extent the use of the system has benefited the institutions and what the reasons why the use of software as a desktop publishing tool, thus being exposed to the advantages and disadvantages. Through the support portal and Dean of Research and Graduate UFPA, electronic journals interested in publishing and maintaining an electronic publication received due support. Presently there are four magazines that use the system and benefit from its advantages: (1) Amazônica: Revista de Antropologia; (2) Novos Cadernos NAEA; (3) Hendu: Revista Latino Americana de Direitos Humanos e (4) Revista de Análise ao Comportamento. The results of research conducted around these institutions show benefits before the production, dissemination and collaboration with the scientific community. The new information technologies are highly interconnected with the new form of scientific communication, thus making the SEER, which is a free system, provided by IBICT very relevant. The importance that one has to use the system and open the door to a production of an electronic publication is intrinsically linked with the fact that the scientific community of the UFPA be something active in science, thus producing new perspectives and knowledge to the future of society.